A Modified Technique for Measuring Shrinkage of Clay Soils - M. I., Tariful; Wan Harun, Wan Sulaiman; D., Ahmad (Universiti Putra Malaysia Press, 1999)
The American Society for Testing and Materials D427 and D4943 methods for volumetric shrinkage were modified using sand, a non-toxic natural material, instead of mercury and wax respectively. The modified method (sand) was compared with the D427 (mercury) and D4943 (wax) methods for measuring volumetric and linear shrinkage. The sand method gave similar results as the mercury and wax methods for shrinkage of samples of three clay soils taken from three different depths. There was no significant difference between the three methods used to measure the shrinkage. Therefore the sand method is a useful alternative because it is environmentally friendly, safe and cheaper to use compared to the mercury and wax methods.